Curricular articulation in practicum: an echo of change - Reis, Isabel; Sarmento, Teresa; Silva, Carlos (Revista Hipótese, 2021)
This study, carried out as part of a Basic Education internship, aims to analyse the potential of curricular integration in the construction of transversal competences. It starts from the contextualization of the center of interest of a group of children from a Kindergarten on the theme of animals and a 3rd year class of Primary School concerning sustainable development. It is intended that the outcomes learnings contribute to the formation of conscious, informed and proactive citizens, based on building a spiral of knowledge, in which the contents and competences have a conceptual, procedural and attitudinal dimension that complement each other.